J10 Chorea, psychotic symptoms and long survival in a subject with ELAC2 mutations. (13th September 2016) - Paucar, Martin; Pajak, Aleksandra; Freyer, Christoph; Stranneheim, Henrik; Wedell, Anna; Wredenberg, Anna; Svenningsson, Per
Abstract : ElaC ribonuclease 2 (ELAC2 ) has been identified as a subunit of the RNaseZ complex, associated with the processing of mtDNA-encoded transcripts. Mutations in the ELAC2 gene are associated with a very rare autosomal recessive mitochondrial disease which phenotype consists of hypertrophic cardiomyopathy and usually death during childhood. Movement disorders have not been described as part of the ELAC2-associated disease spectrum. Here we present a 68 year old female with chorea, cognitive decline, waddling gait, olfactory hallucinations, diabetes and hearing loss. Her motor features and cognitive decline have been slowly progressive. EMG revealed myopathy but a muscle biopsy revealed only mild abnormalities. MRI and FDG-PET scan of the brain revealed widened perisylvian sulci and reduced metabolism in these regions. Huntington's disease and other Huntington phenocopies were ruled out first (Pathological expansions for c9orf72, SCA17 and HDL2 as well as mutations in the PRNP gene). Further investigations with whole exome sequencing revealed the new trans variants c.394G>A and c.1040C>T in the ELAC2 gene. Surprisingly repeated echocardiography has been normal. Although we did not find any evidence of respiratory chain defect in the muscle biopsy, molecular characterisation of patient fibroblasts revealed the accumulation of unprocessed mitochondrial transcripts but normal steady-state levels of mitochondrial mRNAs and tRNAs. Furthermore, patient fibroblasts showed severe growth impairment, when using galactose as energy source. Together, we suggest that mutations in ELAC2 are not exclusively confined to a severe paediatric disease, but also can mimic Huntington's disease.